Impact and outcome of cardiac diseases in pregnancy - Dabhi, Gira; Chauhan, Jignesh; Pandya, Munjal; Sinhar, Rahul (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Present study done to study incidence, effect of pregnancy on cardiac disease and vice-versa and feto-maternal outcome in patients with cardiac disease in pregnancy at tertiary care hospital. Methods: It’s a retrospective observational study conducted in Department of OBGY at tertiary care hospital between 01 June 2019 to 31 May 2020. 28 cases of cardiac disease out of 8659 patients registered included in the study. Demographic data like age, parity, etiological factors of cardiac disease, mode of delivery, neonatal outcome noted from case records. Results: In study, 32% were unregistered cases and 10.7% had never sought any medical care before. Majority (53.6%) cases belonged to 20-25 years. Heart disease noted to be more in primipara (35.7%). 71.4% belonged to NYHA class 1+2 and had a relatively uneventful peripartum period. Majority (53.6%) patients had rheumatic valvular disease. Cases of Congenital heart disease were17.8%, pulmonary artery hypertension was 25%, Maternal mortality were 2(7.2%). 46.5% women delivered with caesarean section. PIH (18%) and anemia (7.2%) were most commonly associated conditions. 85.6% women delivered live newborns and full term, pre-term deliveries and IUGR were 71.4%, 17.8% and 10.7% respectively. Conclusions: Rheumatic origin is the most common cardiac disease associated with pregnancy. The availability of early diagnostic techniques and reference to tertiary care centre, timely admission and close monitoring of patient and delivery with multidisciplinary approach include specialized cardiologic care, high risk obstetric support and neonatology expertise can minimize feto-maternal morbidity and mortality. Pre-conceptional counselling, regular antenatal check-ups and contraceptive advice must be included in counselling part.